Factors associated with depression in older carers - Loi, S.; Dow, B.; Moore, K.; Hill, Keith; Russell, M.; Cyarto, E.; Malta, S.; Ames, D.; Lautenschlager, N. (John Wiley and Sons Ltd, 2015)
Objective: Depression is an adverse outcome frequently seen in carers. With the increasing ageing population and reliance on informal carers, this study aims to identify factors associated with depression in carers in the older age group, using factors that have not been previously investigated. Methods: We conducted a cross-sectional analysis of 202 older carers using the Geriatric Depression scale, demographics, personality traits, attitudes to ageing and other carer characteristics. Results: Increased hours spent caring and higher levels of neuroticism were all factors associated with depression. The care-recipient diagnosis, other personality traits, attitudes to ageing, leisure-physical activity (PA) and domestic-PA were not significantly associated with depression. Conclusions: These findings have important implications for interventions to target at-risk carers.